PENDIDIKAN BERINTEGRITAS SEBAGAI FONDASI GENERASI MASA DEPAN - Naftali Kalengkongan, Aurelia; Jessica Claudia Sibi , Paula; Vandea Anika Tumundo, Celine; Febie Sombuk, Susana; Stanly Immanuel Rumainum, Vian; Tji Beng, Jap (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Education plays a crucial role in shaping individuals who are not only intellectually capable but also possess integrity and moral character. Although integrity has become a central focus of national education policy, empirical studies that deeply explore university students’ subjective experiences in interpreting and internalizing integrity within higher education remain limited. This study aims to explore the meaning of integrity from students’ perspectives and to identify the process through which integrity values are internalized in academic life. A qualitative approach with a phenomenological design was employed. Five active university students were purposively selected based on their academic engagement and participation in character education activities. Data were collected through in-depth interviews and non-participant observation and analyzed using a phenomenological analysis method. The findings reveal that integrity is understood as the alignment between thoughts, words, and actions grounded in moral values. The formation of integrity is influenced by educators’ role modeling, a supportive academic environment, reflective experiences in facing moral dilemmas, and self-awareness as part of students’ moral identity. These findings enrich the discourse on integrity-based education in higher education and provide practical implications for developing more contextual and sustainable character development programs. ABSTRAK Pendidikan berperan penting dalam membentuk individu yang tidak hanya cerdas secara intelektual, tetapi juga berintegritas dan bermoral. Meskipun nilai integritas telah menjadi fokus kebijakan pendidikan nasional, kajian empiris yang menggali secara mendalam pengalaman subjektif mahasiswa dalam memaknai dan menginternalisasi integritas di pendidikan tinggi masih terbatas. Penelitian ini bertujuan untuk mengeksplorasi makna integritas dari perspektif mahasiswa serta mengidentifikasi proses internalisasi nilai-nilai tersebut dalam kehidupan akademik. Penelitian menggunakan pendekatan kualitatif dengan desain fenomenologi. Lima mahasiswa aktif dipilih secara purposive berdasarkan kriteria keterlibatan dalam kegiatan akademik dan pengalaman mengikuti pendidikan karakter. Data dikumpulkan melalui wawancara mendalam dan observasi non-partisipatif, kemudian dianalisis menggunakan metode analisis fenomenologis. Hasil penelitian menunjukkan bahwa integritas dimaknai sebagai keselarasan antara pikiran, ucapan, dan tindakan yang berlandaskan nilai moral. Proses pembentukan integritas dipengaruhi oleh keteladanan pendidik, lingkungan akademik yang suportif, pengalaman reflektif dalam menghadapi dilema moral, serta kesadaran diri sebagai bagian dari identitas moral mahasiswa. Temuan ini memperkaya kajian tentang pendidikan berintegritas di pendidikan tinggi dan memberikan implikasi praktis bagi pengembangan program pembinaan karakter yang lebih kontekstual dan berkelanjutan.